Evaluation of the biological monitoring system as an important tool in the management of Sagay marine reserve, Sagay City, Negros Occidental - Limates, Vilma G. (University of the Philippines in the Visayas, 2003)
A study evaluating the Biological Monitoring System conducted by the Office of the Protected Area Superintendent Sagay Marine Reserve as an important tool for the sustainable management of the protected area. The method used was ana analysis of the biological monitoring system data and feedback of the respondents as to the relative differences and similarities of the average fish catch, income and catch composition of the fishers. Subsequebtly, the reasons for the relative differences and similarities of data were determined and its corresponding implications were identified when evaluated based from the 1994 situation of Sagay's coastal barangays. The feedback or the answers of the respondents showed that Sagay Marine Reserve has certainly sustained the first catch, income and catch composition of the fishers, however, it was not significantly experienced by the fishers because of increased fishing pressure attributed to the rapid population increase and limited livelihood activities in the area. There were relative differences and similrities of data. Specifically, the Biological Monitoring Result on the average catch per trip was relatively higher in contrast to the feedback of the municipal fishers. The average income of fishers based from the interview was similar to the income of the hook and line fishers of Old Sagay if based on the Net Present Value of the money, however it is not enough to provide the needs of the fishers family. There was an improvement of the catch composition considering that some of the exotic species in 1994 were already seen abundant in the area. The identification of reasons on the differences and similarities of data were ascribed to socio-cultural, economic, political, technological, institutional and ecological factors taht were implicated in program implementation, the conduct of the biological monitoring and the method used in the study. Although the respondents were aware of the conduct of the biological monitoring system of SMR, their participation is very limited in the process. They desired to be actively involved in the monitoring and evaluation and were very much in favor of a multi-sectoral monitoring scheme for the protected area. The analysis of the result and the recommendations of the 76 respondents cmposed of 40 municipal fishers from barangay Molocaboc and Barangay Old Sagay, and 36 respondents from the group of stakeholders were used in determining the effectiveness and efficiency of the Biological Monitoring System of Sagay marine Reserve. It served as the basis of the modification of the existing system to maximize the needed information and easy analysis of result useful for the effective and efficient management of the area.